2018
DOI: 10.1177/0003489418757251
|View full text |Cite
|
Sign up to set email alerts
|

Solid Variant of Aneurysmal Bone Cyst of the Temporal Bone

Abstract: Solid variant of ABCs are rare lesions of the skull base that present a diagnostic challenge given their unique radiographic and histologic features. Thorough cytogenetic evaluation is warranted to rule out potential malignant secondary causes. Early surgical resection is essential due to the risk of intracranial extension. This is the first report of ABC of any type with concurrent involvement of the squamous, mastoid, and petrous portions of the temporal bone and the first report of SVABC of the temporal bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…A review of the literature indicated that there have been 21 patients with aneurysmal bone cysts in the temporal bone, with the most common sites of involvement being the petrous apex, the squamous portions and the mastoid. [7][8][9] Very few cases involve the internal auditory canal. Symptoms of aneurysmal bone cysts depend on the location and size of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature indicated that there have been 21 patients with aneurysmal bone cysts in the temporal bone, with the most common sites of involvement being the petrous apex, the squamous portions and the mastoid. [7][8][9] Very few cases involve the internal auditory canal. Symptoms of aneurysmal bone cysts depend on the location and size of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[18][19][20][21][22][23] This is usually associated with resolution of symptoms and an uneventful postoperative course; however, recurrences have been reported. Other options include the use of cement, phenol, cryotherapy, and sclerotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Per our review of the current literature, cases of aneurysmal bone cysts of the skull base are surgically resected. 1,2,[18][19][20][21][22][23] This is usually associated with resolution of symptoms and an uneventful postoperative course; however, recurrences have been reported. 19,21,22 Denosumab has been reported to provide meaningful clinical and radiological improvement in aneurysmal bone cysts.…”
Section: Discussionmentioning
confidence: 99%
“…39 It commonly calcify within 2 to 4 months after embolization. 40 This therapy is usually helpful for ABCs in head and neck regions those are difficult to resect because of their locations like deep seated sites. The embolization techniques are often done before surgical resection.…”
Section: Medicalmentioning
confidence: 99%